Numerical Computations of Separability Probabilities. Issue 2 (October 2016) - Fei, Jianjia; Joynt, Robert
Abstract : We compute the probability that a bipartite quantum state is separable by Monte-Carlo sampling. This is carried out for rebits, qubits and quaterbits. We sampled 5 × 10 11 points for each of these three cases. The results strongly support conjectures for certain rational values of these probabilities that have been found by other methods.